Bone marrow MSCs in MDS: contribution towards dysfunctional hematopoiesis and potential targets for disease response to hypomethylating therapy - Zhiyong Poon; Niraja Dighe; Subhashree Venkatesan; Alice M.S. Cheung; Xiubo Fan; Sudipto Bari; Monalisa Hota; Sujoy Ghosh; William Ying Khee Hwang (2018)
The study of myelodysplastic syndromes (MDS) in murine models has now indicated the possible involvement of the bone marrow microenvironment in the generation of dysplastic hematopoietic cells. However, there is scant work on patient samples and the role of hypomethylating agents on the bone marrow stromal cells of MDS patients is unclear. We show that human MDS-MSCs exhibit phenotypic, transcriptomic and epigenetic abnormalities. Stimuli provided by MDS-MSCs impaired the growth and function of healthy HSPCs, which is further sustained autonomously in HSPCs for significant periods of time resulting in a failure for active hematopoietic engraftment across primary and secondary transplant recipients (chimerism: 0.34–91% vs 2.78%, engraftment frequencies: at 0.06 ± 0.02 vs full engraftment for MDS-MSC vs healthy groups, respectively). Hypomethylation of MDS-MSCs improved overall engraftment in most of the MDS-MSC groups tested (2/7 with p < 0.01, 3/7 with p < 0.05 and 2/7 with no significant difference). MDS-MSCs that fail to respond to hypomethylating therapy are associated with patients with rapid adverse disease transformation and this further suggests that MDS-MSCs may be an integral part of disease progression and have prognostic value as well as potential as a therapeutic target.